2016
DOI: 10.3390/ijms17101667
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Supported Physical Exercise Training for Persons with Multiple Sclerosis—A Randomised, Controlled Study

Abstract: Physical exercise is effective in improving functional outcomes in persons with multiple sclerosis (pwMS). We evaluated the feasibility and effectiveness of internet-based exercise training (e-training) for pwMS on health-related quality of life (HrQoL). Secondary outcomes were muscle strength, aerobic capacity, lung function, physical activity, and fatigue. This is a randomised, controlled trial with a wait-list control group. Data were collected at baseline, after three and six months, and analysed using a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 33 publications
0
80
0
1
Order By: Relevance
“…35,36 To our knowledge, this is the first telephone-delivered exercise program for persons with MS. Other telemedicine approaches have been utilized; the protocols for exercises delivered, including frequency, intensity, type of exercise, or tracking confirmation of performed exercises, were heterogeneous. A 12-week study with the Internet delivery of content recommending 2 times per week of strength training and 1 time per week of endurance training targeting health-related quality of life resulted in improved fatigue 37 but included individuals who were both fatigued and not fatigued. Similarly, a 12-week smartphone-delivered program targeting physical activity in persons with MS fatigue resulted in improved fatigue severity 38 but only reminded participants to stay active and did not specifically recommend exercises or guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 To our knowledge, this is the first telephone-delivered exercise program for persons with MS. Other telemedicine approaches have been utilized; the protocols for exercises delivered, including frequency, intensity, type of exercise, or tracking confirmation of performed exercises, were heterogeneous. A 12-week study with the Internet delivery of content recommending 2 times per week of strength training and 1 time per week of endurance training targeting health-related quality of life resulted in improved fatigue 37 but included individuals who were both fatigued and not fatigued. Similarly, a 12-week smartphone-delivered program targeting physical activity in persons with MS fatigue resulted in improved fatigue severity 38 but only reminded participants to stay active and did not specifically recommend exercises or guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…The only difference was the method of delivery (Table 1). Furthermore, this study was not limited to persons with relapsing-remitting MS, 37,38 those taking a particular disease-modifying therapy, 38 and those with a score of less than 4 on Expanded Disability Status Scale, 37,38 as was common in other telemedicine studies. Finally, prior studies using telemedicine approaches have utilized only survey measures of fatigue, measured at a single time point pre-and postintervention.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, appreciation of the MS TeleCoach by its users was confirmed by a post-study evaluation of patient satisfaction in a subset of study completers. As a comparison, a teleconference-delivered fatigue management program for pwMS (Finlayson et al, 2011) reported more than 90% of completers and an internet-supported physical exercise training for pwMS (Tallner et al, 2016) had a completer rate of 61%. With 76% completers, our study had an intermediate percentage of completers.…”
Section: Discussionmentioning
confidence: 99%
“…describe objective activity levels with accelerometer data. [21][22][23][24] A focus on activity levels may be appropriate for people with mild-to-moderate MS. For people with more advanced disability and in the absence of clear exercise guidelines for those with more advanced MS, it would seem appropriate to first consider participation adherence (i.e., is the person safely participating in regular exercise? ).…”
mentioning
confidence: 99%